Masculinization of featherfin squeaker Synodontis eupterus Boulenger, 1901 larvae using javanese long pepper extract Piper retrofractum and increased rearing temperature - Euis Rakhmawati; Muhammad Zairin Jr; Dinar Tri Soelistyowati (Jurnal Iktiologi Indonesia, 2019)
Javanese long pepper (Piper retrofractum) is known to have androgenic effect, could act as phytosteroid and alternative to masculinization. This research aimed to evaluate the optimum dose of the Javanese long pepper extracts combined with increased rearing temperature on featherfin squeaker masculinization through larva immersion. This research was designed using a completely randomized design with 8 treatments consisted of Javanese long pepper extract doses of 0.0625 mg L-1and 0.125 mg L-1, negative control (without both extract and 17α-metiltestosterone) and positive control (2 mg L-117α-metiltestosterone). Each of them consisted of two different temperature treatments, namely, normal (26-27ᴼC) and 32ᴼC. After five hours treatment, larvae were reared until five months age. The fish age four and then five months were dissected and their gonads were taken for acetocarmine and histology preparation. Beside that the percentage of fish survival, body length, weight gain, and specific growth rate were also recorded in certain period. The result showed that the Javanese long pepper extract dose at 0.125 mg L-1 with normal temperature treatment produced the highest male ratio and significantly different compare with control. Giving this dose to larvae did not affect fish survival and growth, meanwhile increased temperature treatment could not increase the effectivity of Javanese long pepper extract. Abstrak Cabe Jawa dikenal memiliki efek androgenik, yang dapat berperan sebagai fitosteroid dan menjadi alternatif untuk penjantanan. Penelitian ini bertujuan mengevaluasi dosis optimum ekstrak Piper retrofractum yang dikombinasikan dengan peningkatan suhu terhadap penjantanan sinodontis melalui perendaman larva. Peningkatan suhu pemeliharaan dilakukan guna meningkatkan efektivitas dari perlakuan. Penelitian didesain menggunakan rancangan acak lengkap dengan 8 perlakuan terdiri atas perlakuan ekstrak cabe Jawa dosis 0,0625 mg L-1 dan 0,125 mg L-1, kontrol negatif (tanpa ekstrak dan 17α-metiltestosteron) serta kontrol positif (2 mg L-117α-metiltestosteron). Tiap perlakuan terdiri atas dua perlakuan suhu normal (26-27⁰C) dan suhu yang ditingkatkan (32ᴼC). Setelah perendaman lima jam, larva dipelihara sampai berumur lima bulan. Ikan umur empat dan lima bulan dibedah lalu gonadnya diambil untuk pem-buatan preparat histologis dan asetokarmin. Selain itu persentase sintasan, panjang, bobot, dan laju pertumbuhan harian juga dicatat pada periode tertentu. Hasil penelitian menunjukkan bahwa pemberian ekstrak cabe Jawa dosis 0,125 mg L-1 dalam suhu normal menghasilkan nisbah jantan tertinggi dan berbeda signifikan dengan kontrol. Pem-berian dosis ini tidak memberikan efek negatif terhadap sintasan kan dan pertumbuhan, sedangkan peningkatan suhu tidak dapat meningkatkan efektivitas ekstrak cabe Jawa.